Nonthermal resection device for ablation of Barrett’s esophagus: a feasibility and safety study - Gotink, Annieke W.; Peters, Yonne; Bruno, Marco J.; Siersema, Peter D.; Koch, Arjun D. (Endoscopy, 2021)
Background Several techniques exist for the eradication of Barrett’s esophagus (BE); however, all have limitations regarding successful conversion to squamous epithelium and a complication profile. We aimed to assess the feasibility and safety of a new nonthermal device, the EndoRotor, for the eradication of BE as a first-line ablation technique.Methods Patients with BE were prospectively included at two tertiary referral centers in The Netherlands. Inclusion criteria: BE length 2–5 cm, with low grade dysplasia, high grade dysplasia, or residual BE after endoscopic resection (ER) of a lesion containing early neoplasia. Exclusion criteria: previous ER > 50 % circumference, or previous ablation therapy. Follow-up endoscopy was performed 3 months after ablation therapy. Outcomes were the percentage of endoscopically visible BE surface regression and complications.Results 30 patients were included (age 66 years, interquartile range [IQR] 59–73, median BE C0M3, 25 male). Overall, 18 patients underwent ER prior to ablation. Median percentage BE ablated was 100 % (IQR 94 %–100 %). Median visual BE surface regression at 3-month follow-up was 80 % (IQR 68 %–95 %). Multiple residual Barrett’s islands were commonly seen. Six patients (20 %) had a treatment-related complication requiring intervention, including one perforation (3 %), one postprocedural hemorrhage (3 %), and four strictures (13 %). Post-procedural pain was reported in 18 patients (60 %).Conclusions Endoscopic ablation of BE using this novel nonthermal device was found to be technically demanding, with a longer procedure time compared with established ablation techniques and a high complication rate. Based on these results, we do not recommend its use as a first-line ablation technique for the eradication of BE.